ACCOUNTS RECEIVABLE MANAGEMENT AT PT SARANA METAL INDAH IN SURABAYA - Indarti Indarti; Reswanda Reswanda (STKIP Singkawang, 2021)
This research takes the title Accounts Receivable Management. The need to find cash and credit sales to manage receivables that generate profit in the company in order to meet liquidity. The purpose of this study is to analyze the process of managing accounts receivable carried out by the company and to optimize the management of accounts receivable carried out by the company to meet liquidity.The research method used is descriptive with a qualitative approach. This research takes place at PT Sarana Metal Indah Surabaya which is on Jl. Tenggilis Timur 7 DD 18 No 27. The data collection technique was done by collecting methods through observation, interviews, documentation and triangulation. Data collection uses secondary and primary data.The results show that the company's credit sales have increased in the last three years and the collection of accounts receivable has increased rapidly so that the collection of results can be rotated by the company according to their needs. The existence of an effective and efficient accounts receivable management is able to make the company get more profit in order to meet liquidity.Suggestions are expected that companies in carrying out receivables collection activities can be better and management is expected to be able to provide discounts or discounts on credit sales. Discounts or discounts that can be given by the company if the customer pays in full earlier than the predetermined date or the due date that has been agreed by both parties. In addition, it is hoped that the research results can serve as a guide for further researchers in developing this research for the results of the problems that have been discussed.